Metodología para la gestión de riesgos asociados al suministro de medicamentos de alto costo (2022)
The supply of high-cost drugs in pharmaceutical services involves a set of critical processes that often generate economic losses for these organizations. The absence of standardized processes, together with the high probability of errors associated with the handling of these drugs, are part of a recurring panorama that imposes the need to implement effective strategies to mitigate these losses within these organizations. As a strategy, the proposed methodological guide for the management of risks associated with the supply of high-cost drugs is presented, which is developed in six (06) steps that include: discrimination of the context; risk identification; the classification of the risk; risk analysis; risk assessment; and finally, the treatment, monitoring and review of risk. All this structured from the NTC-ISO 31000: 2018 standard, which allows it to become a tool that is easy to implement, and highly useful for treating the different risks that arise with the drug supply process. This methodological guide has been developed from a descriptive method of reviewing sources and qualitative and quantitative data.